Recovery of a dilated left ventricle after cessation of cocaine and HVAD (TM) explanation using a titanium plug - Elbayomi, Mohamed; Weyand, Michael; Seitz, Tatjana; Heim, Christian; Steger, Katrin; Tandler, Rene (Journal of Cardiac Surgery, 2022)
The ultimate goal in the treatment of end-stage heart failure is the recovery of cardiac function following mechanical assistance of the left ventricle. The HVAD (TM) pump (HeartWare Inc.) left ventricular assist device (LVAD) can be explanted without resternotomy. This article illustrates that the usage of a custom-made mechanical plug (manufactured by INNOVO Solutions GmbH), which can be inserted into the LVAD's sewing ring, is feasible. This mechanical plug explicitly designed for device explantation is a viable alternative to the current standard of care. This article adopts a less invasive technique to explant the pump. The following case illustrates this technique.
CRIS-Team WoS Importer:2022-11-25